Cerebrospinal Flt3 ligand correlates to tau protein levels in primary Sjögren's syndrome. (October 2013) - Dehlin, M; Bjersing, J; Erlandsson, M; Andreasen, N; Zetterberg, H; Mannerkorpi, K; Bokarewa, M
Abstract : Objectives: Primary Sjögren's syndrome (pSS) is an autoimmune disease affecting the exocrine glands and internal organs including the central nervous system (CNS). The fms-related tyrosine kinase 3 ligand (Flt3L) is a maturation factor essential for brain homeostasis. Blood levels of Flt3L are increased in inflammatory diseases including the inflamed salivary glands in pSS. The present study evaluated the role of Flt3L in the CNS of patients with pSS and in two non-autoimmune conditions, fibromyalgia (FM) and Alzheimer's disease (AD). Method: Levels of Flt3L were measured in cerebrospinal fluid (CSF) and serum of patients with pSS (n = 15), FM (n = 29), and AD (n = 39) and related to CNS symptoms and to markers of inflammation and degeneration. Results: Levels of CSF Flt3L in pSS and AD were significantly lower than in FM (p = 0.005 and p = 0.0003, respectively). Flt3L in pSS correlated to tau proteins [total tau (T-tau), r = 0.679; phosphorylated tau (P-tau), r = 0.646] and to a marker for microglia activation, monocyte chemoattractant protein 1 (MCP-1). Similar correlations were present in FM and AD patients. One-third of pSS patients had low levels of CSF Flt3L. This group had decreased levels of amyloid precursor protein metabolites (Aβ40 and Aβ42) in CSF, which was not seen in FM patients. Conclusions: This study shows a strong correlation between CSF Flt3L and tau proteins in pSS patients suggesting ongoing degradation/remodelling in the CNS. In pSS patients, low levels of Flt3L were linked to changes in amyloid turnover and may represent processes similar to those in AD.